Estratigrafia Química (COT, δ13C, δ18O) e Nanofósseis Calcários na Passagem Pliensbaquiano–Toarciano no Perfil de Peniche (Portugal): Resultados Preliminares - DE OLIVEIRA, LUIZ CARLOS VEIGA; DUARTE, LUIS VITOR; PERILLI, NICOLA; RODRIGUES, RENÉ; LEMOS, VALESCA (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> The marl-limestone succession that encompasses the Pliensbachian–Toarcian Stage Boundary (Lower Jurassic) and crops out at Peniche (Lusitanian Basin, Portugal), was chosen as one of the candidates for the establishment of Toarcian GSSP. Chemostratigraphy analyses, of the Upper Pliensbachian (spinatum Zone)-Lower Toarcian (levisoni p.p. Zone) portion, were based on total organic carbon (TOC) (68 samples), the isotope carbon (δ13C) and oxygen (δ18O) (38 samples) on the whole rock sample. Presenting an absolute variation of around -2.0‰, the δ13C and δ18O values decrease from the middle part up to the uppermost part of spinatum Zone, with smaller values in the lowermost part of the polymorphum Zone. In the Lower Toarcian the δ13C data shows a positive trend (spread of + 2.0‰) with a maximum value in the middle-upper portion of the polymorphum Zone and a minimum in the lowermost part of the levisoni Zone. The δ18O values show a general tendency to decrease within the polymorphum Zone, with the smallest values observed in the lower portion of the levisoni Zone. In general the TOC values are low, around 0.2%, in the spinatum Zone, upwards they increase to 0.5% in the polymorphum Zone, whilst they decrease again to 0.2% in the lowermost levisoni Zone. Calcareous nannofossils assemblages were investigated in 12 slides of marly samples collected around the Pliensbachian – Toarcian Stage Boundary that, according to the adopted zonation, proposed for NW European, lies in the NJ5b biozone. Abundant and well preserved nannofossils assemblages comprise 12 genera and 18 species. The genera Schizosphaerella and Lotharingius are dominant. Calcivascularis jansae, a characteristic taxon of the Lower Jurassic tethyan nannofossils assemblages, is abundant in the whole investigated interval. Biscutum grande is the other tethyan taxon present in studied succession. The occurrences of C. jansae and B. grande support the tethyan affinity of the calcareous nannofossils assemblages recovered from the Pliensbachian – Toarcian transition sampled at Peniche section.